Nutrient essentiality revisited. (April 2015) - Jew, Stephanie; Antoine, Jean-Michel; Bourlioux, Pierre; Milner, John; Tapsell, Linda C.; Yang, Yuexin; Jones, Peter J.H.
Highlights: Evaluation of essentiality for food constituents currently considered non-essential. Nutrient essentiality could be for a specific population or physiological condition. Fibre and plant sterols could be considered essential for those with high cholesterol. Establishing the essentiality of polyphenols requires further investigation. Abstract: With increased understanding of the complex roles nutrients play within metabolic pathways, the purpose of this contribution is to explore the rationale for expanding the definitions and criteria for nutrient essentiality. A further objective was to develop three case study scenarios to probe issues surrounding the definition of essentiality using dietary fibre, plant sterols and polyphenols. Current definitions and criteria for "essentiality" were reviewed through an environmental scan of the scientific literature. Additionally, international regulatory bodies were asked whether the terms "nutrient" and/or "essential nutrient" are regulated in their respective jurisdictions. Regulatory bodies including the EFSA, the US FDA, HC and FSANZ were found not to currently possess regulated definitions for the term "essential nutrient". Case studies examining fibre, plant sterols and polyphenols served as a means of presenting evidence for expanding the list of functional food constituents regarded as meeting criteria for essentiality. For each example, certain instances applied where these case study bioactives met criteria of essentiality. Thus, in order to reflect advances in current science, a series of non-classical compounds known to have bioactivity should be considered for their potential essentiality under certain situations.